The evolution of the SovietAmerican economic cooperation in 1920s – early 1930s - Petachenka, Ryhor A.; Shabasava, Maryna A. (Journal of the Belarusian State University. History, 2023)
The aim of the article is the examination of the different types of the Soviet-American economic cooperation in the 1920s – early 1930s. It is emphasised that the Soviet rulers admitted the need of borrowings of the advanced technique, technologies and the labour organisation from the Western countries, especially from the USA. The special attention is paid to the process of the choosing of suitable forms of economic cooperation. The practice of granting and curtailing of concessions in the 1920s is explored. It is shown the from the mid 1920s American businessmen were suppressed by both the Soviet government and trade unions. The authors analyse the role of the American leftists and reemigrants in the restoration of the Soviet economy. The examples of the industrial and agrarian colonies are given. The contribution of the USA to the fulfillment of the first five-year plan is scrutinised. The authors examine American participation in the designing of the Soviet enterprises, the ways of getting American loans, procurements of American technical equipment. The authors conclude that all forms of the Soviet-American economic cooperation between the countries were short-lived and practiced only for a few years. That did not allow the Soviets to use the potential of economic cooperation with the USA to the full extent.
Keywords: new economic policy; concession; industrialisation; USSR; USA; the Soviet-American economic cooperation